Evaluation du respect de calendrier vaccinal chez les enfants pygmées en âge de 0-59 mois - ZANIWE, Félix-Amand FUFULAFU; WOWO, Innocent BULUPIY (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2021)
The topic of our researh or study is entitled « The Evaluationof the observance of the pygmy children’s vaccinal calender in the uebanand rural health area/ zone of Isiro. Vaccination has a considerable impact on infantile morbility and mortality. Millions of enfants continue dyng every year because of vaccination avoidable diseases (by vaccination). In France, almost 23.5 millions of thidren are no always vaccinated completely every year due tho the lack of vaccine, two millions of enfants die in countries in positionof devellopmentt of vaccination avoidablee deseases (USAIDet al ,2006). In isiro town and its surrondingswe have noticed that certain pygmey children aged of 0to 11 monthshave no access to different antigins of routine PEV : (Elarged vaccine program). Taking into account what goos above, te following questions are to by asked : What would be the proportion of pygmy children who respect the vaccinal calender ? What would be the factors hyndering the observance of the vaccinalcalendar on the port of these children ? What could be the strategees susceptibles to increase the vaccinal acces in the children ? to the reach these results . The following objectives have been fixes : To determine the proportion of pygmy infants who respect the vaccinal calendar. To spicify factors limiting the access of these children to the vaccination To propose the strategies to make agreat deal of these infants to the respect of the vaccinal calendar The descriptive transversal, ethod has served to the realization of the recherch followed by the direct trace of BCG scar at thefoream of each child. Furthermore we have checed the vaccination form fo each kid. The main results below have been noted or listed : 100% of pygmy children did not respect the vaccination calender 94 % of pygmy kids did not have the BCG scar at the left forearm 100% of these pygmy children had nod the CPS form 16% of the investigated infants were in the 25 to 29 weeks of age-group 3 of the pygmy kids are borna t the maternity hospital 43% of these pygmy children’s mothers indicate by ignorencethe deltoid muscle as the site or place of the BCG vaccine injection 60% of caises had a namber of 3 to 5 pygmy infants 41% of pygmy sensititess were nurses. The pygmy children are ot vaccinated in Isiro and its surrounndings. The congolese government through its minister of public health must initiate the autchonous pygmypeople’s itegration programme in the sensitization in ordeer to accept the vaccine to avoid these mortal diseases. This alson necessitates te participation of international and national organizations for the success of the investigation of pygymies’ health activities in its totality.